Rural nursing : concepts, theory, and practice - Winters, Charlene A.; Lee, Helen J. (Helen Jacobsen), 1935- (Springer Pub. Co., 2010)
"Bona Drag, a rich, brilliantly inventive collection of poems covering every detail of the poet's obsessive life, from the colour of Posh Spice's heels, to London street encounters, underworld friends, urban survival tactics, neuroscientific concepts and extraterrestrials, more than confirms J.G. Ballard's assessment of Reed, as "the most gifted poet working today, an extraordinary talent.""--Jacket.